Analisis Perbandingan Reksa Dana Saham Syariah dengan Reksa Dana Saham Konvensional Periode 2009–2012 - Mulya Riyady Esha; Mohamad Heykal; Titik Indrawati (Binus Business Review, 2014)
The purpose of this study is to measure performance of sharia equity fund compared conventional equity fund and to find out whether the performance of sharia equity fund and conventional equity fund could outperform the market. The research method is annual return, risk adjusted return, and snail trail. The research object is equity fund that has been stated effective by Bapepam – LK before the research period. Result from this study is sharia equity fund has a better performance, a few of equity fund can outperform from the market, and the result of statistic test declares that there is not any different average performance of sharia equity fund and conventional equity fund with Significance level (0.05). Conclusion of the study is sharia equity fund have better performance and it could be compared with conventional equity fund.